Misi Dan Pelayanan Sosial: Jejak Badan Zending RMG Di Tanah Batak (1861-1940) - Samosir, Jetti (JURNAL DIAKONIA, 2024)
The mission and social services carried out by missionaries in the Batak Land in the 19th century have had a significant impact on the Batak people. Mission and social services are intertwined. From the outset, missionary activities have been closely linked to the development of Batak community infrastructure, including churches, hospitals, educational facilities, and the economy, often referred to as "pargodungan." Mission and social services have provided overall benefits to the Batak community. In this article, the author will elaborate on the Mission and Social Services conducted by the RMG Missionary Society in the Batak Land (1861-1940), starting with an overview of the establishment of the HKBP (Batak Christian Protestant Church).